Psychological Confusion and Its Relationship to Some Psychological Features of Taekwondo Players - Diaa Fadel Abbas; Zaid Sami yasir; Hayder Naji Habash Alshawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the research lies in the identification of psychological frequency and some psychologicalfeatures that players face in taekwondo competitions and to find the degree of correlation between them, andthe problem of the research was through the work of researchers in the field of the taekwondo game. Oneof them has different psychological characteristics from the other, so the researchers decided to study thisproblem by determining this frequency, determining the psychological characteristics, and then knowing therelationship between them and whether there is an effect of one of them on the other to develop appropriatesolutions in the service of Taekwondo players, and the research objectives were to prepare the psychologicalfrequency scale, And the identification of psychological frequency and some psychological features ofadvanced Taekwondo players, and knowledge of the relationship between psychological frequency andsome psychological features of advanced Taekwondo players, the researchers used the descriptive approachon some Taekwondo players in the Najaf Sports Club for the sports season (2019-2020) of (30) A playerthrough the results of the results, the researchers reached the following conclusions. The players of the IraqiPremier League with Taekwondo appeared as having an amputation. A weak psychological and high selfconfidence trait, which increased their motivation for achievement in the competition, the players showedhigh psychological energy optimal for advanced Taekwondo players, which reduced their psychologicalreluctance to compete, and the presence of an inverse moral correlation between psychological hesitationand some psychological features (self-confidence - psychological fluency ) For players of the PremierLeague Taekwondo.